MRI versus conventional measures of disease activity and structural damage in evaluating treatment efficacy in juvenile idiopathic arthritis. Issue 3 (4th July 2012) - Malattia, C; Consolaro, A; Pederzoli, S; Madeo, A; Pistorio, A; Mazzoni, M; Mattiuz, C; Magnano, GM; Viola, S; Buoncompagni, A; Palmisani, E; Hasija, R; et al.
Abstract : Objective: To compare the American College of Rheumatology paediatric (ACRp) response criteria and conventional radiography with MRI findings in a cohort of patients with juvenile idiopathic arthritis. Methods: Forty consecutive patients (30 girls, 10 boys; median age 10.8 years) with arthritis of the wrist starting treatment with disease-modifying antirheumatic drugs or biological agents were recruited. At 1-year follow-up the treatment response was assessed by ACRp criteria and radiographic progression using the adapted Sharp/van der Heijde method. Wrist MRIs were evaluated using both the paediatric-MRI and the OMERACT rheumatoid arthritis MRI scores. Sensitivity to change of clinical and imaging variables was assessed by standardised response mean (SRM) and relative efficiency (RE) was used to compare SRMs. Results: ACRp90 responders showed a significantly higher decrease in MRI synovitis score (median change −4) than non-responders (median change 0), ACRp30–50 responders (median change 0) and ACRp70 responders (median change −1) (p=0.0006, Kruskal–Wallis test). Non-responders showed significantly higher radiographic progression than ACRp90 responders (pB=0.016). The MRI synovitis score showed a greater responsiveness to change (SRM 1.69) compared with the majority of ACR core set of variables. MRI erosion scores were less responsive than conventional radiography in detecting destructive changes (RE <1). MRI follow-up revealed no signs of inflammation in four out of 24 wrists with clinically inactive disease. Conclusion: Only ACRp90 responders showed a significant decrease in synovitis and the halting of structural damage, suggesting that levels of response higher than ACRp30 are more appropriate for assessing drug efficacy. The excellent responsiveness of MRI and its ability to detect subclinical synovitis make it a promising outcome measure.